Modeling of laser wakefield acceleration in Lorentz boosted frame using a Quasi-3D OSIRIS algorithm - Yu, P. (2021)
Recently it was proposed in [A. F. Lifschitz, et. al., J. Comp. Phys. 228, 1803 (2009)] that laser wakefield acceleration could be modeled efficiently using a particle-in-cell code in cylindrical coordinates if the fields and currents were expanded into Fourier modes in the azimuthal angle, ?. We have implemented this algorithm into OSIRIS, including a new rigorous charge conserving deposition routine applicable for it [A. Davidson, et. al., J. Comp. Phys. 281, 1063 (2014)]. This algorithm can be interpreted as a PIC description in r - z and a gridless description in ? in which the expansion into ? modes is truncated at a desired level. This new quasi-3D algorithm greatly reduces the computational load by describing important three-dimensional (3D) geometrical effects with nearly two-dimensional calculations. In this paper, we propose to combine this algorithm with the Lorentz boosted frame method for simulations of Laser wakefield acceleration (LWFA). We show preliminary results, including an investigation of the unstable numerical Cerenkov instability modes for this geometry, and discuss directions for future work. These preliminary results indicate that combining the quasi-3D method and the Lorentz boosted frame method together may provide unprecedented speed ups for LWFA simulations.